Recognizing & engaging employees for dummies - Nelson, Bob 1956- (For dummies., 2015)
A guide to improving morale, productivity, and personal achievement at work. Nelson walks you step-by-step through incentives and mechanisms that must be in place for a recognition and engagement program to be effective in the long term.